PENGARUH KEPEMIMPINAN, KOMPENSASI DAN KOMPETENSI TERHADAP MOTIVASI KERJA KARYAWAN PT. TUJUH CAHAYA BINTANG ABADI - Elvie Maria (Universitas Methodist Indonesia, 2018)
The purpose of this reseach is to examine the effect of leadership, compensation and competence on work motivation. This research collected samples from 95 employees using a proportionate random sampling technique. The data was analyzed by using a multiple linier regression. The of the study states that the contribution of variable leadership, compensationd and competence variables, to explain work motivation variables is 78.9%. Next, the data analysis explained that leadership, compensation and competence simultaneously and partially have a significant effect on work motivation.